Building capacity for health informatics in the future (Studies in health technology and informatics, 2017)
This book presents the proceedings of the 2017 Information Technology and Communications in Health conference (ITCH 2017), held in Victoria, BC, Canada, in February 2017. The conference considers, from a variety of perspectives, what is required to move the technology forward to real, sustained and widespread use, and the solutions examined range from improvements in usability and training to the need for new and improved design of information systems, user interfaces and interoperable solutions. Government policies, mandates, initiatives and the need for regulation are also explored, as is the requirement for improved interaction between industrial, governmental and academic partners